Caffeine and Placebo Improved Maximal Exercise Performance Despite Unchanged Motor Cortex Activation and Greater Prefrontal Cortex Deoxygenation - Pires, Flavio O.; dos Anjos, Carlos A. S.; Covolan, Roberto J. M.; Fontes, Eduardo B.; Noakes, Timothy D.; St Clair Gibson, Alan; Magalhães, Fernando H.; Ugrinowitsch, Carlos (Frontiers in Physiology, 2018)
Caffeine (CAF) is an ergogenic aid used to improve exercise performance. Independent studies have suggested that caffeine (CAF) may have the ability to increase corticospinal excitability, thereby decreasing the motor cortex (MC) activation required to generate a similar motor output. However, CAF has also been suggested to induce a prefrontal cortex (PFC) deoxygenation. Others have suggested that placebo (PLA) may trigger comparable effects to CAF, as independent studies found PLA effects on motor performance, corticospinal excitability and PFC oxygenation. Thus, we investigated if CAF and CAF-perceived PLA may improve motor performance, despite the likely unchanged MC activation and greater PFC deoxygenation. Nine participants (26.4 ± 4.8 years old, VO2MAX of 42.2 ± 4.6 mL.kg-1.min-1) performed three maximal incremental tests (MIT) in control (no supplementation) and 60 min after CAF and PLA ingestion. PFC oxygenation (near-infrared spectroscopy at Fp1 position), MC activation (EEG at Cz position) and vastus lateralis and rectus femoris muscle activity (EMG) were measured throughout the tests. Compared to control, CAF and PLA increased rectus femoris muscle EMG (P = 0.030; F = 2.88; d = 0.84) at 100% of the MIT, and enhanced the peak power output (P = 0.006; F = 12.97; d = 1.8) and time to exhaustion (P = 0.007; F = 12.97; d = 1.8). In contrast, CAF and PLA did not change MC activation, but increased the PFC deoxygenation as indicated by the lower O2Hb (P = 0.001; F = 4.68; d = 1.08) and THb concentrations (P = 0.01; F = 1.96; d = 0.7) at 80% and 100% the MIT duration. These results showed that CAF and CAF-perceived PLA had the ability to improve motor performance, despite unchanged MC activation and greater PFC deoxygenation. The effectiveness of CAF as ergogenic aid to improve MIT performance was challenged.